Preliminary results of a multidisciplinary Italian study adopting a Psycho-Neuro-Endocrine-Immunological (PNEI) approach to the study of colorectal adenomas - Mancini, Stefano; Alboni, Silvia; Mattei, Giorgio; Rioli, Giulia; Sena, Paola; Marchi, Mattia; Sacchetti, Andrea; Boarino, Valentina; Roncucci, Luca; Galeazzi, Gian Maria; Ferrari, Silvia (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work Colorectal mucosal precancerous lesions, metabolic syndrome (MetS) and psychiatric disorders may share a common low-grade local and systemic inflammation. Aim is to report on preliminary data concerning a research adopting a psycho-neuro-endocrine-immune (PNEI) approach to study outpatients undergoing colonoscopy. Methods A sample of patients undergoing colonoscopy was cross-sectionally investigated. Data on colorectal adenomas, MetS, early atherosclerosis, anxious-depressive symptoms, personality traits, and inflammatory markers were statistically analyzed. Results Sixty-two patients were recruited (female 50%, mean age: 60.8±9.4 years). The prevalence of adenomas and MetS was respectively of 45.2% and 41.9%. Anxiety and depressive symptoms were detected in 16 (32.7%) and 9 (18.4%) subjects, respectively. The presence of adenomas positively correlated with male sex (p=0.01), age (p